A Comparison of Arthroscopically Assisted Single and Double Bundle Tibial Inlay Reconstruction for Isolated Posterior Cruciate Ligament Injury - Shon, Oog Jin (The Korean Orthopaedic Association, 2010)
BACKGROUND: This study evaluated the clinical results of arthroscopically assisted single and double bundle tibial inlay reconstructions of an isolated posterior cruciate ligament (PCL) injury. METHODS: This study reviewed the data for 14 patients who underwent a single bundle tibial inlay PCL reconstruction (Group A) and 16 patients who underwent a double bundle tibial inlay PCL reconstruction (Group B) between August 1999 and August 2002. The mean follow-up period in groups A and B was 90.5 months and 64 months, respectively. RESULTS: The Lysholm knee scores in groups A and B increased from an average of 43.3 ± 7.04 and 44.7 ± 5.02 preoperatively to 88.1 ± 7.32 and 88.7 ± 9.11 points at the final follow-up, respectively. In group A, stress radiography using a Telos device showed that the preoperative mean side-to-side differences (SSDs) of 9.5 ± 1.60 mm at 30° of flexion and 9.8 ± 1.70 mm at 90° of flexion were improved to 2.8 ± 1.19 mm and 3.0 ± 1.1 mm, respectively. In group B, the preoperative SSDs of 10.4 ± 1.50 mm at 30° of flexion and 10.7 ± 1.60 mm at 90° of flexion improved to 2.7 ± 1.15 mm and 2.6 ± 0.49 mm, respectively. There was no significant difference in the clinical scores and radiologic findings between the two groups. CONCLUSIONS: Single bundle and double bundle PCL reconstructions using the tibial inlay technique give satisfactory clinical results in patients with an isolated PCL injury, and there are no significant differences in the clinical and radiological results between the two techniques. These results suggest that it is unnecessary to perform the more technically challenging double bundle reconstruction using the tibial inlay technique in an isolated PCL injury.